Calpain2 Upregulation Regulates EMT-Mediated Pancreatic Cancer Metastasis via the Wnt/β-Catenin Signaling Pathway - Peng, Xiulan; Yang, Rui; Song, Jia; Wang, Xia; Dong, Weiguo (Frontiers in Medicine, 2022)
Calpains2 (CAPN2) is a calcium-dependent, nonlysosomal cysteine protease that plays critical roles in normal cellular functions and pathological processes, including tumorigenesis, cancer progression and metastasis. However, the role and underlying regulatory mechanisms of CAPN2 in pancreatic cancer (PC) are still unknown. We found that CAPN2 is highly expressed in PC tissues and associated with poor PC prognosis by using The Cancer Genome Atlas (TCGA) datasets, Gene Expression Omnibus (GEO) datasets, and PC tissue arrays. CAPN2 downregulation significantly inhibited cell proliferation, migration, and invasion and regulated Wnt/β-catenin signalling pathway-mediated epithelial-mesenchymal transition (EMT) in PC cells. Our findings highlight the significance of CAPN2 in tumour regression and thus indicate that CAPN2 could be a promising target for PC treatment.